To what extent are temperature levels changing due to greenhouse gas emissions? - John K. Dagsvik; Sigmund H. Moen (Statistics Norway, Research Department, 2023)
Weather and temperatures vary in ways that are difficult to explain and predict precisely. In this article we review data on temperature variations in the past as well possible reasons for these variations. Subsequently, we review key properties of global climate models and statistical analyses conducted by others on the ability of the global climate models to track historical temperatures. These tests show that standard climate models are rejected by time series data on global temperatures. Finally, we update and extend previous statistical analysis of temperature data (Dagsvik et al., 2020). Using theoretical arguments and statistical tests we find, as in Dagsvik et al. (2020), that the effect of man-made CO2 emissions does not appear to be strong enough to cause systematic changes in the temperature fluctuations during the last 200 years.
Keywords: C22; C46; Q54; 330; Global climate models; Climate change; Temperature analysis; Fractional Gaussian noise; Long-range dependence